Enhancement of Oral Bioavailability of Rosuvastatin Using Combinational Approach of Thermal Fraction of Clarified Butter (Asian Journal of Pharmaceutics (AJP), 2021)
Background: Thermal fractionation is an effective technique similar to chromatographic separation. Clarified butter(CB) is a mixture of fatty acid which shown different physiochemical properties if fractionated by various means.The present investigation was a study of the suitability of 30°C and 50°C thermal fractions of CB in various ratiosfor improvement of absorption of poorly aqueous soluble drug rosuvastatin (RSC). This work also tries to addressthe difficulty in in vitro dissolution data correlation with in vivo absorption characteristics in a practical situation.Aim: The author aims to get the best combination of 30°C and 50°C fractions which give desirable drug release witheffective permeation. Materials and Methods: The 32 factorial design approach was used to formulate rosuvastatinCB complex using thermal fractions in various ratios. Drug CB complex was evaluated in various parameters suchas contact angle, partition coefficient, saturation solubility, dissolution, and permeation characteristics. The changein physical and chemical properties of drug complex prepared with various ratios of the thermal fraction was alsostudied by X-ray diffraction and Liquid Chromatography-Mass Spectroscopy. Results and Discussion: The weightratio of thermal fraction of CB (TFCB) fractionated at 30°C and TFCB fractionated at 50°C in 1:1.5 w/w informulation RAE-B2 was found suitable to improve the absorption characteristics of rosuvastatin. The ex vivopermeation studies showed 90.68% permeation of rosuvastatin from RAE-B2 formulation which was found tohigher than other formulation as well as pure rosuvastatin. Conclusion: The result suggested that the drug complexprepared using 30°C and 50°C fractions at 1:1.5 shown optimum drug release with desired permeation.